Interleukin-2 as a marker for detecting asymptomatic individuals in areas where Leishmania infantum is endemic. (August 2016) - Ibarra-Meneses, A.V.; Carrillo, E.; Sánchez, C.; García-Martínez, J.; López Lacomba, D.; San Martin, J.V.; Alves, F.; Alvar, J.; Moreno, J.
Abstract: No field method exists for identifying asymptomatic individuals in areas where Leishmania infantum is endemic. This work reports that, 24 h after stimulating whole blood with soluble Leishmania antigen (SLA), plasma interferon-γ (IFN-γ) and interleukin-2 (IL-2) become significantly elevated in samples from asymptomatic individuals ( n  = 47) compared with those from negative controls ( n  = 50), all of them recruited from a blood bank. When compared with the reference test SLA-lymphoproliferative assay, IL-2 appears as a new, 100% sensitive and specific marker for asymptomatic individuals with a positive cellular response (compared with 100% and 84.78%, respectively, for IFN-γ). Further studies in other transmission areas and in other cohorts of exposed people need to be performed to confirm these results. Once validated, IFN-γ and IL-2 levels in SLA-stimulated whole blood could be reliably used in the field to estimate the prevalence of those asymptomatic individuals with Leishmania -specific cellular immune responses.